(untitled) (Journal of Hama University, 2020)
An experimental feeding trial was conducted to study the impact of different Methionine sources on performance and oxidation status of broiler chickens . A total of 510 One-day-old Ross (308) chicks were randomly assigned into six equal groups. (G1) was fed on basal diets with DL-M, (G2) was fed on the same diets with DL-M & BHT, (G3) was fed on the same diets with MHA-FAK, (G4) was fed on the same diets with MHA-FA (BE 65%) & BHT, (G5) was fed on the same diets with MHA- Ca, and (G6) was fed on the same diets with MHA-Ca & BHT. Results revealed significant (P< 0.05) positive effects of either DL-Met or MHA-Ca or in combination with BHT supplementation on most of the growth performance parameters, meanwhile the broiler chicks responded lesser to MHA-FA than DL-Met. None of serum parameters were affected except for the elevated levels of ALT of chicks in groups (G3 and G4). The highest (GSH), (CAT), (GPx) and (GR) and lowest significant MDA levels were also observed in the birds supplemented with DL-Met+ BHT (G2) and those supplemented with DL-Met alone (G1), also Mitochondrial Oxygen Consumption test as well as Mitochondrial function alteration in livers improve a situation that indicated the ability of both DL-Met or MHA-Ca to improve the oxidation status of the birds and confirmed the positive impact noticed in growth performance traits. The highest and significant (BMY%), were recorded in the birds supplemented with DL-Met+ BHT (G2) and those supplemented with DL-Met (G1).But the other carcass traits including organ indices seem to be not significantly altered . In addition groups received DLMet or MHA-Ca with or without fortification of BHT showed an increase in villus height and villus to crypt ratios. It could be concluded that the use of both D-Met and MHA-Ca with or without BHT supplementation had a better effect not only on growth performance, serum parameters carcass traits and gut morphology but also alleviated oxidative stress in broilers chickens. Knowing and understanding the relative biological value (RBV) of MHA-FA compared to DL-Met is an important precondition to cost-effective purchasing, feed formulation and broiler production.